ELECTRONIC TRANSACTIONS IN INDONESIA RELATED TO USE THE THEORY OF “LEX INFORMATICA” AND THE CONCEPT OF “SELF REGULATION” - Priowirjanto, Enni Soerjati (Department of Transnational Business Law, Faculty of Law Universitas Padjadjaran, 2020)
The basis of electronic transaction is the free will from everyone who bind himself to others, without coercion from any party, and without the necessity to meet directly. This requires regulations other than the existing law as guidelines for the perpetrators. The agreement is made under lex Informatica, particularly the rules made and agreed upon by the parties in electronic transaction. This article is written to discuss the use of lex Informatica concerning the self-regulation approach carried out along with its examples of electronic transaction in Indonesia. The focus of the discussing is about the benefits of using lex Informatica in electronic transaction and the relation between lex Informatica and self-regulation as theory and approacch in electronic transaction. This study using juridical normative research methods, and descriptive-analytical specifications, through library research and field studies. The results obtained indicate that lex Informatica as a fondation law in internet can underlying an agreement between the parties regarding matters that are not regulated in statutory regulations and self-regulation relating to lex Informatica can be as a regulatory model that provides an opportunity for parties to regulates electronic transaction activities.